PROFIBROTIC MACROPHAGE POLARIZATION AND REPROGRAMMING IN PRECISION CUT LUNG SLICES - Kumaran, Vaishnavi (My University, 2024)
Idiopathic pulmonary fibrosis (IPF) is a progressive lung disease with worsening respiratory symptoms and physiological impairment. Pulmonary fibrosis is a chronic lung disease characterized by forming scar tissue (fibrosis) in the lungs. Alternatively activated macrophages (M2) known as pro-fibrotic are known to contribute to the fibrotic remodeling of the lung. In addition to the polarization of slices from naïve to pro-fibrotic, the addition of anti-fibrotic therapeutics reprogram slices back to a naïve condition. To polarize the slices, naïve slices are incubated with a previously investigated method in the lab known as the polarization cocktail. The polarization cocktail can be achieved by adding of IL-4, IL-6 and IL-13 to naïve(M0) slices in the Precision Cut lung slice (PCLS) model. For the therapeutic model, slices are incubated with the polarization cocktail and subsequently with the therapeutic. Our results have shown that the precision cut lung slice model can mimic previously investigated in-vivo experiments with the polarization cocktail. Secondly, the addition of therapeutics result in the slices exhibiting lower amounts of M2 markers and arginase activity concluding the model is suitable for the polarization and reprogramming of macrophages.
Keywords: Idiopathic pulmonary fibrosis; IPF; PCLS; Alternatively activated macrophage; M2; M1; Classically activated macrophage; Interstitial lung disease; Fibrotic lung disease; IHC; TGF-B; Beta-glucan; Microparticle; Yeast-Derived Beta Glucan; Ex vivo Models